Group 4 constrained geometry complexes for olefin (co)polymerisation - Williams, TJ; Smith, ADH; Buffet, J-C; Turner, ZR; O'Hare, D (Elsevier, 2020)
We report the synthesis and characterisation of eight constrained geometry complexes, with variation of the amido fragment, ansa-bridge, permethylindenyl group, metal centre and initiator groups from the parent complex Me2SB(tBuN,I*)TiCl2. These complexes have been shown to be highly active for slurry-phase ethylene polymerisation when supported on solid polymethylaluminoxane (sMAO), with activities up to 7048 kgPE/molTi/h/bar. Ethylene/1-hexene and ethylene/styrene copolymerisations have shown these complexes to be good incorporators of comonomers into the polymer chain.